Diastereoselective construction of a library of structural bispiro[butyrolactone/valerolactone–pyrrolidine–indanedione] hybrids via 1, 3-dipolar cycloaddition reactions. (8th June 2022) - Zhang, Lei; Quan, Wei; Liu, Ren-Ming; Tian, You-Ping; Pan, Bo-Wen; Liu, Xiong-Li
Abstract : The first example of the introduction of a spiroindanedione moiety into a spirobutyrolactone framework. Abstract : Herein, a highly efficient strategy that allows the diverse synthesis of a library of structural bispiro[butyrolactone–pyrrolidine–indanedione] hybrids is achieved effectively for the first time by means of 1, 3-dipolar cycloadditions of α, β-unsaturated butyrolactones/valerolactones as dipolarophiles with azomethine ylides (thermally generated in situ from ninhydrin and proline or thioproline) via an exo′-transition state. Potentially bioactive target compounds have been obtained in good yields and diastereoselectivities (up to 89% yield and all cases >20 : 1 dr).